PENGARUH PERILAKU KONSUMEN DAN LABEL HALAL PRODUK MAKANAN RUMAH TANGGA TERHADAP KEPUTUSAN KONSUMSI DI PALANGKA RAYA - Rahmaniar Rahmaniar; Fuad Farid; Yeni Herliani (AL-QARDH, 2017)
Every individual has different manners for making choices, including choosing a need and desire. In the modern world of today has come a wide selection of products both local and international standards one of which is a food product. Namely food production in the country for food products imported from abroad, as well as processed food products such as cottage industries. Existing halal label on food products would have been very impact and influence for consumers, particularly Muslim consumers are encouraged to consume Thayyib food and halal. For this study will focus on the effect of consumer behavior and halal label food products by household to consumption decisions in Palangka Raya (Student Association of Islamic Economics at IAIN Palangka Raya) to determine the effect of consumer behavior and halal label food products by households to consumption decision analysis techniques Correlation Product Moment using SPSS 18.0. This research is quantitative descriptive research type ex post facto, and perform data analysis with multiple regression test. Data collection methods the authors used observations and questionnaires. From the test result perfomed on the instrument 20 respondents to the question number 40 items declared valid and can be used to collect the data in the study sample. The population in this study were all students of Islamic Economics at IAIN Palangka Raya in force from 2012 to 2015. While the study sample were 75 respondents students of Faculty of Islamic Economics and Business, Departement of Islamic Economics at IAIN Palangka Raya, and from the number of respondents were given a questionnaire to be answered. Data analysis technique used is Multiple Regression. The result of this study indicate that obtained from the F test (simultaneous) amounted tp 7.132, then in accordance with the F test criteria then Ho is rejected. This means that there are significant effect between consumer behavior and halal label together or simultaneously on consumption decisions, the results obtained from the value of R Square of 0.165 which means that the consumer behavior variables (X1) and label halal food products household (X2) 16,5% have influence on consumer decision variable (Y). while the remaining 83,5% is influenced by other factors.